2015
DOI: 10.5812/ijem.24618v2
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of Determinants of Obesity-Related Behaviors in Adolescents: Development and Psychometric Characteristics

Abstract: Background:The rising prevalence of childhood obesity is a major health problem worldwide. Hence, there is a growing need for health professionals to become capable of assessing the factors that determine lifestyle in a culturally relevant manner.Objectives:This study aimed to develop and assess a questionnaire for measuring determinants of obesity-related behaviors in Tehranian adolescents.Patients and Methods:Based on the results of a qualitative study and an extensive literature review, the 44-item “Invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…In other words, majority of staffs had excess body weight (BMI>25) (26.2% obese and 53.4% overweight). These results were against the local reports showing high prevalence of overweight and obesity provided from reports on the Demographic Information and Health status of Iranians [32,33] and other Middle Eastern countries [34,35] . The mean age of the respondents in this study was 37.18 ± 7.06 years.…”
Section: Resultscontrasting
confidence: 78%
“…In other words, majority of staffs had excess body weight (BMI>25) (26.2% obese and 53.4% overweight). These results were against the local reports showing high prevalence of overweight and obesity provided from reports on the Demographic Information and Health status of Iranians [32,33] and other Middle Eastern countries [34,35] . The mean age of the respondents in this study was 37.18 ± 7.06 years.…”
Section: Resultscontrasting
confidence: 78%
“…The prevalence of obesity and overweight during childhood has dramatically increased during the last decades [ 1 , 2 ]. World Health Organization (WHO) reported that 39 million children under the age of five were overweight or obese, in 2020 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, obesity is increasing in most countries of the world (1), which according to Iranian studies is no exception to this (2). Obesity in childhood is a problem that endangers the health of the child.…”
mentioning
confidence: 99%
“…Obesity in childhood is a problem that endangers the health of the child. Obesity in childhood can be the cause of obesity in adulthood (2)(3). Obesity can carry risks such as type 2 diabetes, plasma lipid deficiency (4), and cardiovascular disease and hypertension (5).…”
mentioning
confidence: 99%